Development of Logistics Technologies and Programs to Reduce Warehouse Costs (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This paper examines the role of logistics technologies and programs in reducing warehouse costs. It discusses the impact of automation, advanced inventory management systems, and data analytics on warehouse operations. The paper provides insights into the benefits of adopting these technologies and the potential challenges faced during implementation. Key findings highlight the importance of integrating these technologies to achieve cost-effective and efficient warehouse management. Technological Advancements in Warehousing.